Sintered body, powder and method for producing same
Patent Information
- Application Number
- JP2020068126
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-25
- Filing Date
- 2020-04-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-04-06
AI Technical Summary
【0009】 本開示により、常圧焼結によって得られるジルコニア焼結体であって、SEPB法により測定される破壊靭性値が高いジルコニア焼結体を得るための原料、当該原料から得られる焼結体、及びこれらの製造方法の少なくともいずれかを提供するができる。
Smart Images

Figure 0007608726000001 
Figure 0007608726000002 
Figure 0007608726000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sintered body having zirconia as a main phase, a powder serving as a raw material thereof, and a method for producing the same. [Background technology]
[0002] In addition to conventional applications requiring strength, such as grinding media and structural materials, zirconia sintered bodies are being considered for use in decorative applications such as decorative parts for watches, portable electronic devices, automobiles, home appliances, etc. Sintered bodies used for decorative applications are required to have reduced brittleness, i.e., high fracture toughness.
[0003] Various zirconia sintered bodies have been reported so far with the aim of improving the fracture toughness value. For example, Patent Document 1 reports a zirconia-alumina composite sintered body obtained by mixing a commercially available 3 mol % yttria-containing zirconia powder produced by a neutralization coprecipitation method with a commercially available alumina powder to prepare a mixed powder, and then sintering the mixed powder with microwaves. The fracture toughness value (K IC ) is 6.02 to 6.90 MPa m 1 / 2 It is stated that:
[0004] Patent Document 2 reports a zirconia sintered body obtained by subjecting zirconia powder containing phosphorus, silicon dioxide, and alumina to hot isostatic pressing (HIP). The sintered body has a fracture toughness value of 6 to 11 MPa m, measured according to the method specified in JIS R 1607. 1 / 2 It is stated that: [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-226555 A [Patent Document 2] JP 2011-178610 A Summary of the Invention [Problem to be solved by the invention]
[0006] The zirconia sintered bodies disclosed in Patent Documents 1 and 2 are difficult to apply industrially because they need to be prepared by applying special sintering methods such as microwave sintering and HIP treatment. However, when applying them to decorative parts, it is also required to evaluate the brittleness of the sintered body with a highly reliable fracture toughness value. In response to this, there are multiple methods for measuring fracture toughness, even though they are standardized, and the values obtained by each measurement method are significantly different. The fracture toughness value in Patent Document 1 is a value measured by a simple method, and the measurement method for the fracture toughness value in Patent Document 2 is unclear, and the values disclosed in both documents are unreliable.
[0007] An object of the present disclosure is to provide at least one of a raw material for obtaining a zirconia sintered body obtained by normal pressure sintering and having a high fracture toughness value measured by the SEPB method, a sintered body obtained from the raw material, and a method for producing the same. [Means for solving the problem]
[0008] The gist of the present disclosure is as follows. [1] A sintered body comprising zirconia containing a stabilizer and having a monoclinic ratio of 0.5% or more. [2] The sintered body according to the above [1], wherein the ratio of the integrated intensity of the XRD peak corresponding to the (111) plane of monoclinic zirconia to the integrated intensity of the XRD peak corresponding to the (11-1) plane of monoclinic zirconia is 0 or more. [3] The sintered body according to the above [1] or [2], wherein the stabilizer is one or more selected from the group consisting of yttria, calcia, magnesia and ceria. [4] The sintered body according to any one of [1] to [3] above, wherein the content of the stabilizer is 1.0 mol % or more and less than 2.5 mol %. [5] Fracture toughness measured using the SEPB method specified in JIS R1607 is 6 MPa m 0.5More than 11MPa m 0.5 The sintered body according to any one of the above [1] to [4], [6] The sintered body according to any one of the above [1] to [5], further comprising one or more additive components selected from the group consisting of alumina, germania and silica. [7] The sintered body according to any one of the above [1] to [6], wherein the additive component is alumina. [8] The sintered body according to any one of the above [1] to [7], wherein the zirconia contains monoclinic zirconia and at least one of tetragonal zirconia and cubic zirconia. [9] A sintered body according to any one of [1] to [8] above, in which the ratio of the tetragonal crystal ratio after immersion treatment in hot water at 140°C for 6 hours to the tetragonal crystal ratio before immersion treatment in hot water at 140°C for 6 hours is 15% or more.
[10] A method for producing a sintered body according to any one of the above [1] to [9], characterized in that a powder is used which contains a stabilizer, contains zirconia having a monoclinic ratio of more than 70%, and has a crystallite diameter of more than 23 nm and not more than 80 nm.
[11] A powder comprising a stabilizer, zirconia with a monoclinic fraction exceeding 70%, and a crystallite diameter of the monoclinic zirconia exceeding 23 nm and not exceeding 80 nm.
[12] The powder according to
[11] above, wherein the zirconia crystal phase comprises monoclinic zirconia and tetragonal zirconia.
[13] The powder according to the above
[11] or
[12] , wherein the stabilizer is one or more selected from the group consisting of yttria, calcia, magnesia and ceria.
[14] The powder according to any one of
[11] to
[13] above, wherein the content of the stabilizer is 1.0 mol% or more and less than 2.5 mol%.
[15] The powder according to any one of
[11] to
[14] above, further comprising one or more additive components selected from the group consisting of alumina, germania and silica.
[16] The powder according to
[15] above, wherein the content of the additive component is 0.1% by mass or more and 30% by mass or less.
[17] BET specific surface area is 6m2 / g or more 20m 2 The powder according to any one of
[11] to
[16] above, wherein the molecular weight is less than 1 / g.
[18] The powder according to any one of
[11] to
[17] above, having a median diameter of 0.05 μm or more and 0.3 μm or less.
[19] A member comprising the sintered body according to any one of [1] to [9] above. Effect of the Invention
[0009] The present disclosure can provide at least one of a raw material for obtaining a zirconia sintered body obtained by normal pressure sintering and having a high fracture toughness value measured by the SEPB method, a sintered body obtained from the raw material, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the present disclosure will be described with reference to an example of an embodiment.
[0011] The terms used in this embodiment are as follows:
[0012] The "monoclinic fraction" and "tetragonal fraction" are the fractions of monoclinic zirconia and tetragonal zirconia in the zirconia crystal phase, respectively. The "monoclinic intensity ratio" is the ratio of the area intensity of the XRD peak corresponding to the (11-1) plane of monoclinic zirconia to the area intensity of the XRD peak corresponding to the (111) plane of monoclinic zirconia in the zirconia crystal phase.
[0013] For powders, the powder X-ray diffraction (hereinafter also referred to as "XRD") pattern of the powder is used, while for sintered bodies, the XRD pattern of the surface of the sintered body after mirror polishing is used, and the monoclinic fraction can be calculated from the following formula (1), the tetragonal fraction from the following formula (2), and the monoclinic intensity ratio from the following formula (3). f m ={I m (111)+I m (11-1)} / [Im (111) +I m (11-1)+I t (111)+I c (111)]×100 (1) f t =I t (111) / [I m (111)+I m (11-1) +I t (111)+I c (111)] × 100 (2) M (11-1) / (111) ={I m (11-1) / I m (111)} (3)
[0014] In formulas (1) to (3), f m is the monoclinic rate (%), f t is the tetragonal crystal ratio (%), M (11-1) / (111) is the monoclinic intensity ratio, I m (111) and I m (11-1) are the integrated intensities of the XRD peaks corresponding to the (111) and (11-1) planes of monoclinic zirconia, respectively, and I t (111) is the area intensity of the XRD peak corresponding to the (111) plane of tetragonal zirconia, and I c (111) is the integrated intensity of the XRD peak corresponding to the (111) plane of cubic zirconia.
[0015] The conditions for measuring the XRD pattern are as follows: Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ=26°~33°
[0016] In the above-mentioned XRD pattern measurement, preferably, the XRD peaks corresponding to the respective crystal planes of zirconia are measured as peaks having peak tops at the following 2θ angles.
[0017] XRD peak corresponding to the (111) plane of monoclinic zirconia: 2θ=31±0.5° XRD peak corresponding to the (11-1) plane of monoclinic zirconia: 2θ=28±0.5° The RD peaks corresponding to the (111) planes of tetragonal zirconia and cubic zirconia were measured in duplicate, and the 2θ angle of the peak top was 2θ=30±0.5°.
[0018] The integrated intensity of the XRD peak of each crystal plane can be determined by separating each XRD peak using the calculation program "PRO-FIT" according to the method described in H. Toraya, J. Appl. Crystallogr., 19, 440-447 (1986).
[0019] In addition, the surface of the sintered body after surface polishing used for the above-mentioned XRD measurement was ground using a surface grinder, and then the measurement surface was mirror-polished in the following order: automatic polishing with an abrasive cloth and paper, automatic polishing with a diamond slurry having an average particle size of 3 μm, and automatic polishing with colloidal silica having a particle size of 0.03 μm, resulting in a sintered body with a surface roughness Ra of 0.04 μm or less.
[0020] "Crystalline diameter of monoclinic zirconia" (hereinafter "D m The "crystallite diameter of tetragonal zirconia" (hereinafter referred to as "D") is a value calculated from the XRD pattern of the powder using the following formula (4). t ") is a value calculated from the powder XRD pattern using the following formula (5). D m =κλ / (βcosθ m ) (4) D t =κλ / (βcosθ t ) (5)
[0021] In formula (4) and formula (5), D m is the crystallite diameter of monoclinic zirconia (nm), D tis the crystallite size of tetragonal zirconia (nm), κ is the Scherrer constant (κ = 1), λ is the wavelength of the light source used for XRD measurement (nm), β is the half-width (°) after correcting for mechanical spreading using quartz sand (Wako Pure Chemical Industries, Ltd.) with a particle size of 25 to 90 μm, and θ m is the Bragg angle (°) of the reflection corresponding to the (11-1) plane of monoclinic zirconia in XRD measurement, and θ t is the Bragg angle (°) of the reflection corresponding to the (111) plane of tetragonal zirconia in XRD measurement. When CuKα radiation is used as the light source for XRD measurement, λ is 0.15418 nm.
[0022] The "BET specific surface area" is a value determined by the BET single-point method in accordance with JIS R 1626-1996, using nitrogen (N2) as the adsorbed substance.
[0023] "Particle size by volume distribution" refers to the particle size of a powder obtained by measuring the volume particle size distribution by a laser diffraction method. The particle size obtained by the laser diffraction method is a non-spherical approximation. The following conditions are given as the conditions for measuring the volume particle size distribution. Measurement sample: Powder slurry Refractive index of zirconia: 2.17 Refractive index of solvent (water): 1.333 Measurement time: 30 seconds Pretreatment: Ultrasonic dispersion treatment
[0024] The term "median size" refers to a particle size corresponding to a volume ratio of 50% on a cumulative volume particle size distribution curve obtained by volume particle size distribution measurement using a laser diffraction method.
[0025] The "particle size distribution curve" is a curve showing the particle size distribution of a powder obtained by volumetric particle size distribution measurement using a laser diffraction method.
[0026] "Fracture toughness" is the fracture toughness value (MPa m) measured by a method conforming to the SEPB method specified in JIS R 1607. 0.5) The fracture toughness value is measured using a columnar sintered body sample with a support distance of 30 mm, width of 4 mm, and thickness of 3 mm, and the average value of 10 measurements may be used as the fracture toughness value of the sintered body of this embodiment. In addition, JIS R 1607 specifies two methods of fracture toughness measurement, the IF method and the SEPB method. The IF method tends to measure larger values than the SEPB method. Furthermore, since the IF method is a simple measurement method, the measured values vary greatly from measurement to measurement. Therefore, the absolute values of the fracture toughness value in this embodiment and the fracture toughness value measured by the IF method cannot be compared. Similarly, the absolute values of the fracture toughness value measured by a method other than the SEPB method and the fracture toughness value measured by the SEPB method cannot be compared.
[0027] The "bending strength" refers to a three-point bending strength value determined by a three-point bending test in accordance with JIS R 1601. The bending strength is measured using a columnar sintered body sample with a support distance of 30 mm, width 4 mm, and thickness 3 mm, and the bending strength of the sintered body of this embodiment may be determined by averaging the values measured 10 times.
[0028] "Total light transmittance" refers to the total light transmittance for light with a wavelength of 600 nm at a sample thickness of 1.0 mm, and can be measured by a method conforming to JIS K 7361. Light with a wavelength of 600 nm is used as the incident light, and the transmittance can be calculated as the total transmittance value for the incident light, which is the diffuse transmittance and linear transmittance. A sample with a thickness of 1 mm and a surface roughness (Ra) of ≦0.02 μm on both sides (the measurement surface and the surface opposite to the measurement surface) is used as the measurement sample, and light with a wavelength of 600 nm is irradiated onto the sample using a general spectrophotometer (e.g., V-650, manufactured by JASCO Corporation), and the transmittance (diffuse transmittance and linear transmittance) of the sample is measured by collecting the transmitted light using an integrating sphere, which may be regarded as the total light transmittance.
[0029] The term "linear transmittance" refers to the total light transmittance for light with a wavelength of 600 nm when the sample thickness is 0.05 mm to 0.2 mm, preferably 0.05 mm to 0.15 mm, particularly 0.09 mm, and can be measured by a method conforming to JIS K 7361. The linear transmittance can be determined by using light with a wavelength of 600 nm as the incident light. A sample with a thickness of 1 mm and a surface roughness (Ra) of ≦0.02 μm on both sides (the surface to be measured and the surface opposite to the surface to be measured) is used as the measurement sample, and the linear transmittance of the sample is measured by irradiating the sample with light with a wavelength of 600 nm using a general spectrophotometer (e.g., V-650, manufactured by JASCO Corporation) and collecting the transmitted light using an integrating sphere.
[0030] "Relative density" is the ratio (%) of the measured density to the theoretical density. The measured density of a molded body is the ratio (g / cm) of the volume determined by dimensional measurement to the mass measured by mass measurement. 3 ), and the measured density of the sintered body is the ratio of the volume measured by Archimedes' method to the mass measured by mass measurement (g / cm 3 ), and the theoretical density is the density (g / cm) calculated from the following formulas (6) to (9): 3 ). A = 0.5080 + 0.06980X / (100 + X) (6) C=0.5195-0.06180X / (100+X) (7) ρ Z =[124.25(100-X)+225.81X] / [150.5(100+X)A 2 C] (8) ρ0=100 / [(Y A / 3.987)+(Y G / 3.637)+(Y S / 2.2) +(100-Y A -Y G -Y S ) / ρ Z ] (9)
[0031] In equations (6) to (9), ρ0 is the theoretical density, ρ Zis the theoretical density of zirconia, A and C are constants, X is the molar ratio (mol%) of yttria to the total of zirconia (ZrO2) and yttria (Y2O3), and Y A , Y G and Y S are the mass percentages (mass%) of alumina converted into Al2O3, germania converted into GeO2, and silica converted into SiO2 to the total of zirconia, yttria, alumina, germania, and silica of the compact or sintered body converted into ZrO2, Y2O3, Al2O3, GeO2, and SiO2, respectively.
[0032] The sintered body of this embodiment will be described below.
[0033] The present embodiment is a sintered body characterized by including zirconia containing a stabilizer and having a monoclinic ratio of 0.5% or more.
[0034] The sintered body of the present embodiment is a sintered body containing zirconia containing a stabilizer, and is a sintered body having zirconia containing a stabilizer as a main phase, that is, a so-called zirconia sintered body.
[0035] The stabilizer has a function of stabilizing zirconia, and may be one or more selected from the group consisting of calcia (CaO), magnesia (MgO), ceria (CeO2) and yttria (Y2O3), and is preferably at least one of ceria and yttria, more preferably yttria. In the sintered body of this embodiment, the content of the stabilizer may be a content that partially stabilizes zirconia. As the content of the stabilizer, for example, when the stabilizer is yttria, the molar ratio of yttria to the total of zirconia (ZrO2) and yttria (Y2O3) in the sintered body (= {Y2O3 / (ZrO2+Y2O3)}×100 [mol%]; hereinafter, also referred to as "yttria content") can be exemplified as 1.0 mol% or more and 2.5 mol% or less, further 1.1 mol% or more and 2.2 mol% or less, and further 1.1 mol% or more and 2.0 mol% or less, and preferably 1.2 mol% or more and less than 2.0 mol%, and more preferably 1.2 mol% or more and 1.8 mol% or less. By having the stabilizer content in this range, the fracture toughness value measured by the SEPB method tends to be high. The yttria content is preferably 1.4 mol% or more and 2.1 mol% or less, and further preferably 1.5 mol% or more and 1.8 mol% or less.
[0036] The stabilizer is preferably dissolved in zirconia, and the sintered body of this embodiment does not contain any undissolved stabilizer, and it is preferable that all of the stabilizer is dissolved in zirconia, and it is more preferable that the XRD pattern of the sintered body of this embodiment does not have an XRD peak of the stabilizer. In this embodiment, when the XRD peak of the stabilizer can be confirmed as an XRD peak other than the XRD peak of zirconia, it can be considered that the sintered body contains an undissolved stabilizer.
[0037] The sintered body of this embodiment may contain one or more additive components selected from the group consisting of alumina (Al2O3), germania (GeO2) and silica (SiO2). The additive component is preferably at least one of alumina and germania, and more preferably alumina. By containing the additive component, the grain boundary strength between crystal grains is likely to be high even when the content of the stabilizer for zirconia is small. When the additive component is contained, the sintered body of this embodiment is a sintered body containing the additive component and the balance being zirconia containing a stabilizer. The content of the additive component is the mass ratio of the additive component to the total mass of the zirconia, yttria and additive component of the sintered body. For example, the content of the additive component of a sintered body containing alumina as an additive component and the balance being zirconia containing yttria is calculated as {Al2O3 / (ZrO2+Y2O3+Al2O3)}×100[mass%]). The content of the additive component is, for example, 0.05% by mass or more and 30% by mass or less, preferably more than 0.1% by mass or less and 25% by mass or less, and more preferably 0.2% by mass or more and 20% by mass or less. If the content of the additive component is 0.02% by mass or more and 0.3% by mass or less, the mechanical strength tends to be high and transformation to monoclinic zirconia tends to be difficult to occur.
[0038] The sintered body of this embodiment preferably does not contain any impurities other than unavoidable impurities, such as hafnia (HfO2).
[0039] The sintered body of this embodiment has a monoclinic ratio of 0.5% or more, preferably 0.5% to 15%, and more preferably 0.8% to 12%. Since fracture toughness tends to be high, the monoclinic ratio is preferably 1% to 15%, 2% to 14%, 5% to 12%, or 7% to 11%. On the other hand, since bending strength tends to be high, the monoclinic ratio is preferably 0.5% to 5%, and more preferably 0.8% to 3%.
[0040] The surface of the sintered body immediately after sintering (as-sintered surface; hereinafter, also referred to as the "sintered surface") is rough and contains many sources of destruction such as unevenness. In order to prevent the sintered body from being destroyed, the sintered surface is removed by processing such as grinding, and the sintered body is polished to expose a mirror-like surface (polished surface; hereinafter, also referred to as the "mirror surface") prior to evaluation or use in various applications. The mirror surface is, for example, a smooth surface with Ra≦0.04 μm. The monoclinic ratio is the value of the mirror surface of the sintered body. In a conventional sintered body having partially stabilized zirconia as the main phase, after mirror processing such as processing and polishing, the crystal phase is composed of at least one of tetragonal zirconia and cubic zirconia, and contains substantially no monoclinic zirconia or only a small amount of monoclinic zirconia. Furthermore, sintered bodies with low mechanical properties may be destroyed during mirror finishing, and may not be processed into measurement samples, and may even be sintered bodies for which the monoclinic ratio cannot be measured. In contrast, the sintered body of this embodiment has monoclinic zirconia that satisfies the above-mentioned monoclinic ratio on its mirror surface. Therefore, it is considered that the sintered body of this embodiment is a sintered body that has monoclinic zirconia throughout the sintered body, or a sintered body that contains tetragonal zirconia that is likely to transform into monoclinic zirconia.
[0041] In the sintered body of the present embodiment, the zirconia contains monoclinic zirconia and at least one of tetragonal zirconia and cubic zirconia, and is preferably made of monoclinic zirconia and tetragonal zirconia.
[0042] The monoclinic zirconia contained in the sintered body of this embodiment is monoclinic zirconia having at least an XRD peak corresponding to the monoclinic zirconia (111) plane in its XRD pattern. By containing such monoclinic zirconia in a state before the deterioration treatment, the sintered body tends to exhibit a high fracture toughness value and is less susceptible to hydrothermal deterioration. When monoclinic zirconia is generated due to deterioration of the sintered body, the intensity of the XRD peak mainly corresponding to the monoclinic zirconia (11-1) plane in the XRD pattern becomes strong. In contrast, the monoclinic zirconia contained in the sintered body of this embodiment preferably has at least an XRD peak corresponding to the monoclinic zirconia (111) plane in its XRD pattern, and the monoclinic intensity ratio is preferably 0 or more, more preferably 0.3 or more, even more preferably 0.4 or more, and even more preferably 0.5 or more. The monoclinic intensity ratio is preferably 10 or less, 8 or less, 5 or less, 3 or less, or 1.5 or less, and more preferably 1.2 or less, or further preferably 1.0 or less. The monoclinic intensity ratio can be calculated from the formula (3). m In a sintered body in which (111) is zero, i.e., which does not have an XRD peak corresponding to the monoclinic zirconia (111) plane, the monoclinic intensity ratio is infinite and the value cannot be calculated. In other words, it is preferable that the sintered body of the present embodiment does not include a sintered body in which the monoclinic intensity ratio is infinite.
[0043] The average crystal grain size of the zirconia crystal grains in the sintered body of this embodiment varies depending on the sintering temperature, but may be, for example, any one of 0.1 μm to 0.8 μm, 0.15 μm to 0.60 μm, 0.20 μm to 0.55 μm, or 0.25 μm to 0.45 μm.
[0044] The sintered body of this embodiment preferably has a relative density (hereinafter also referred to as "sintered body density") of 98% or more and 100% or less, more preferably 98.4% or more and 100% or less, and even more preferably 99% or more and 100% or less.
[0045] Furthermore, the sintered body of this embodiment is preferably a sintered body obtained by atmospheric sintering (so-called atmospheric sintered body), more preferably a sintered body obtained by atmospheric sintering in an air atmosphere. Also, it is preferable that the sintered body is in a state in which no sintering treatment other than atmospheric sintering has been performed, and more preferably a state in which no sintering treatment has been performed after atmospheric sintering. As the sintering treatment other than atmospheric sintering, one or more selected from the group consisting of pressure sintering, vacuum sintering, and microwave sintering can be exemplified.
[0046] The sintered body of this embodiment has a fracture toughness value (measured according to the SEPB method specified in JIS R1607) of 6 MPa m 0.5 More than 11MPa m 0.5 For example, it is preferably 6.2 MPa m 0.5 More preferably, 7 MPa m 0.5 More preferably, 8 MPa m 0.5 It is preferable that the fracture toughness value is high, for example, 11 MPa m 0.5 Below, and even 10.5MPa m 0.5 or even 9.5MPa·m 0.5 Below 9MPa m 0.5 or even 8.5MPa·m 0.5 The fracture toughness value is preferably 1 mm or less. By having such a fracture toughness value, it is easy to process the sintered body into a sintered body having a thickness of 1 mm or less, and even 0.5 mm or less. As a result, the sintered body of this embodiment may be formed into a sintered body having a thickness of 0.05 mm or more and 0.3 mm or less, or even 0.08 mm or more and 0.25 mm or less.
[0047] The sintered body of this embodiment has a bending strength of, for example, 1000 MPa or more and 1550 MPa or less, further 1100 MPa or more and 1500 MPa or less, preferably 1100 MPa or more and 1460 MPa or less, and more preferably 1200 MPa or more and 1400 MPa or less.
[0048] The sintered body of this embodiment preferably has a total light transmittance of 20% to 50%, more preferably 25% to 45%, and even more preferably 30% to 40%. In particular, when the content of the additive component is more than 0% by mass and 25% by mass or less, more preferably 0.2% by mass to 5% by mass, and even more preferably 0.23% by mass to 3% by mass, the total light transmittance is preferably 20% to 45%, and even more preferably 25% to 40%.
[0049] The sintered body of this embodiment may have a linear transmittance of 1% to 20%, 1% to 15%, or 1% to 10%. The linear transmittance is a value measured on a sintered body having a sample thickness of 0.05 mm to 0.2 mm, preferably 0.05 mm to 0.15 mm, and particularly 0.09 mm. The linear transmittance in this embodiment is a measured value on such a sample thickness, and is different from an estimated value or a calculated value obtained from a linear transmittance measured on a sintered body having a thicker sample thickness, such as a sintered body having a sample thickness of 0.5 mm or more.
[0050] The sintered body of this embodiment particularly preferably has an in-line transmittance of 1% to 10%, 1.5% to 8%, 2% to 7.5%, or 2.5% to 7.3% at a sample thickness of 0.09 mm.
[0051] The tetragonal zirconia contained in the sintered body of this embodiment is preferably resistant to transformation into monoclinic zirconia by hydrothermal treatment (hereinafter also referred to as "hydrothermal deterioration"). The ratio of the tetragonal fraction after immersion in hot water at 140 ° C. for 6 hours to the tetragonal fraction before immersion in hot water at 140 ° C. for 6 hours (hereinafter also referred to as "residual tetragonal fraction" or "ΔT%) is preferably 15% or more, more preferably 70% or more, and even more preferably 80% or more. If tetragonal zirconia is not transformed into monoclinic zirconia by immersion in hot water at 140 ° C. for 6 hours, the residual tetragonal fraction is 100%, so the residual tetragonal fraction in the sintered body of this embodiment is 100% or less, and further 95% or less.
[0052] The more the content of the additive component is, the more the hydrothermal deterioration tends to be suppressed. In the sintered body of this embodiment, when the content of the additive component is 0 mass%, i.e., when the additive component is not included, the residual tetragonal ratio can be 15% or more and 100% or less, preferably 20% or more and 100% or less, more preferably 50% or more and 80% or less. When the sintered body of this embodiment contains the additive component and the content of the additive component is more than 0 mass% and less than 5 mass%, the residual tetragonal ratio can be 65% or more and 100% or less, preferably 70% or more and 90% or less. When the sintered body of this embodiment contains the additive component and the content of the additive component is 5 mass% or more and 30 mass% or less, the residual tetragonal ratio can be 70% or more and 100% or less, preferably 76% or more and 95% or less.
[0053] The shape of the sintered body of this embodiment may be any desired shape, including basic shapes such as a cube, a rectangular parallelepiped, a polygonal body, a plate, a disk, a column, a cone, a sphere, an approximately spherical shape, and other shapes of components suitable for various applications.
[0054] The sintered body of the present embodiment may be produced by any method, but is preferably produced by a method using a powder as a raw material, which contains a stabilizer, contains zirconia with a monoclinic ratio of more than 70%, and has a crystallite size of more than 23 nm and 80 nm or less. After molding such a powder, it may be sintered by a known method. Furthermore, at least one of calcination and processing may be performed before sintering as necessary.
[0055] The molding may be carried out by a known method, for example, at least one method selected from the group consisting of uniaxial pressing, cold isostatic pressing, slip casting, and injection molding, and is preferably at least one method selected from the group consisting of uniaxial pressing, cold isostatic pressing, and injection molding.
[0056] The calcination may be carried out by heat treating the powder at a temperature lower than the sintering temperature, for example, at 800° C. or higher and lower than 1200° C. in the air.
[0057] The sintering may be performed by a known method, such as one or more selected from the group consisting of pressure sintering, vacuum sintering, and atmospheric sintering. As it is simple and easy to apply industrially, atmospheric sintering is preferred, and atmospheric sintering in the air at 1200°C to 1550°C, preferably 1250°C to 1500°C, is more preferred, and atmospheric sintering in the air at 1300°C to 1450°C is even more preferred. It is also preferred not to perform any sintering other than atmospheric sintering.
[0058] The sintered body of the present embodiment can be used as a member containing the sintered body in the applications of known zirconia sintered bodies. The sintered body of the present embodiment is suitable for crusher members, precision machine parts, structural materials such as optical connector parts, biomaterials such as dental materials, decorative members, and exterior materials such as electronic equipment exterior parts.
[0059] The powder of this embodiment will be described below.
[0060] The present embodiment is a powder characterized by containing a stabilizer, including zirconia with a monoclinic ratio of more than 70%, and the crystallite diameter of the monoclinic zirconia being more than 23 nm and not more than 80 nm.
[0061] The powder of this embodiment contains a stabilizer and includes zirconia with a monoclinic ratio of more than 70%. That is, the powder of this embodiment includes stabilizer-containing zirconia mainly composed of monoclinic zirconia. When the zirconia powder does not contain a stabilizer, it is difficult to obtain a sintered body containing tetragonal zirconia, which is a factor in expressing fracture toughness, even if the powder is sintered. The powder of this embodiment is a so-called zirconia powder mainly composed of zirconia.
[0062] The stabilizer may be one or more selected from the group consisting of calcia (CaO), magnesia (MgO), ceria (CeO2) and yttria (Y2O3), preferably at least one of ceria and yttria, more preferably yttria. When the stabilizer is yttria, the molar ratio of yttria (yttria content) to the total of zirconia (ZrO2) and yttria (Y2O3) in the powder may be 1.0 mol% or more and 2.5 mol% or less, or further 1.1 mol% or more and 2.0 mol% or less, preferably 1.2 mol% or more and less than 2.0 mol%, and more preferably 1.2 mol% or more and 1.8 mol% or less.
[0063] The stabilizer is preferably dissolved in zirconia, and the powder of this embodiment preferably does not contain any undissolved stabilizer.
[0064] As the main crystal phases of zirconia, monoclinic zirconia, tetragonal zirconia, and cubic zirconia are known. The zirconia in the powder of the present embodiment includes monoclinic zirconia, and preferably includes at least one of monoclinic zirconia, tetragonal zirconia, and cubic zirconia, and more preferably includes monoclinic zirconia and tetragonal zirconia.
[0065] The monoclinic ratio of zirconia is more than 70%, preferably 80% or more, and more preferably 85% or more. The monoclinic ratio is 100% or less, and when zirconia contains at least one of tetragonal zirconia and cubic zirconia, the monoclinic ratio is less than 100%. The tetragonal ratio is 30% or less, more preferably less than 20%, and is preferably 15% or less, and may be 10% or less, or even 7% or less. When zirconia does not contain tetragonal zirconia, the tetragonal ratio is 0%, and the tetragonal ratio may be 0% or more.
[0066] Monoclinic zirconia crystallite size (D mIn another embodiment, the crystal grain size (D m ) may be 30 nm or more and 50 nm or less, further 35 nm or more and 50 nm or less, and may be 35 nm or more and 45 nm or less, further 36 nm or more and 40 nm or less.
[0067] The powder of this embodiment may contain one or more additive components selected from the group consisting of alumina (Al2O3), germania (GeO2) and silica (SiO2). The additive component is preferably at least one of alumina and germania, and more preferably alumina. By containing the additive component, even if the content of the stabilizer for zirconia is small, defects such as cracks are unlikely to occur during sintering, and the yield during sintering is unlikely to decrease. The content of the additive component is, as a mass ratio of the additive component to the total mass of zirconia, yttria and the additive component of the powder, 0.05 mass% or more and 30 mass% or less, preferably more than 0.1 mass% and 25 mass% or less, more preferably 0.2 mass% or more and 20 mass% or less, and even more preferably 0.23 mass% or more and 6 mass% or less.
[0068] The powder of the present embodiment preferably does not contain impurities, and for example, the phosphorus (P) content is 0.1 mass% or less and less than 0.1 mass%, respectively. On the other hand, the powder may contain inevitable impurities such as hafnia (HfO2) of zirconia.
[0069] The powder of this embodiment has a BET specific surface area of 6 m 2 / g or more 20m 2 For example, the BET specific surface area is less than 6 m 2 / g or more, sintering can proceed easily at a relatively low temperature. 2 By setting the BET specific surface area to less than 8 m / g, physical aggregation of the powder tends to be suppressed. 2 / 18m or more2 / g or less, more preferably 10m 2 / g or more 17m 2 / g or less, more preferably 10m 2 / g or more 15m 2 / g or less, and even more preferably 10m 2 / g over 15m 2 / g or less.
[0070] The powder of this embodiment preferably has a median diameter of 0.05 μm or more and 0.3 μm or less, and more preferably 0.1 μm or more and 0.2 μm or less.
[0071] The powder of this embodiment may have a multimodal volume particle size distribution curve, and the volume particle size distribution curve may have peaks at least at particle sizes of 0.05 μm to 0.2 μm and more than 0.2 μm to 0.5 μm, and more preferably at particle sizes of 0.05 μm to 0.2 μm and more than 0.3 μm to 0.5 μm. Powders having a multimodal volume particle size distribution curve, such as a bimodal distribution, tend to have high filling properties during molding. Since the density of the resulting molded body tends to be high, the ratio of the peak of the particle size of 0.3 μm to 0.5 μm in the volume particle size distribution curve to the peak of the particle size of 0.05 μm to 0.2 μm (hereinafter also referred to as the "particle size peak ratio") is preferably more than 0 and less than 1, more preferably 0.1 to 0.9, and even more preferably 0.2 to 0.8.
[0072] The powder of this embodiment preferably has high moldability, and when the powder of this embodiment is uniaxially press molded at a pressure of 70±5 MPa and then treated with cold isostatic pressing (hereinafter also referred to as "CIP") at a pressure of 196±5 MPa to form a molded body, the relative density of the molded body (hereinafter also referred to as "molded body density") is preferably 49% or more and 56% or less, and more preferably 50% or more and 54% or less.
[0073] The powder of this embodiment may contain a resin for improving fluidity, or may be a composition (hereinafter, also referred to as a "compound") containing the powder of this embodiment and a resin. The resin contained in the compound may be any known resin used in ceramic compositions, such as a thermoplastic resin. Preferred examples of the resin include one or more of the group consisting of acrylic resin, polystyrene, and polyalkyl carbonate, and preferably acrylic resin.
[0074] The content of the powder in the compound can be, for example, 50% by mass to 97% by mass, 70% by mass to 95% by mass, or 80% by mass to 90% by mass. The content of the powder in the compound can be calculated from the mass ratio of the compound after removing the resin to the mass of the compound. The resin can be removed by any method, but can be, for example, heat treatment at 200°C to 500°C in air.
[0075] In addition to the resin, the compound may contain components such as wax as additives. The inclusion of these components provides additional effects such as improved releasability from the mold. Examples of components such as wax include one or more selected from the group consisting of polyethylene, polypropylene, polyacrylonitrile, acrylonitrile-styrene copolymer, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, polyacetal resin, petroleum wax, synthetic wax, vegetable wax, stearic acid, phthalate ester plasticizer, and adipic acid ester.
[0076] The powder of this embodiment can be used as a precursor for calcined bodies or sintered bodies, and is suitable as a raw material powder for structural materials such as pulverizer components, precision machinery parts, and optical connector parts, biomaterials such as dental materials, and exterior materials such as decorative components and exterior parts for electronic devices.
[0077] When the powder of this embodiment is to be made into a sintered body or the like, the powder may be molded and then calcined or sintered by a known method.
[0078] When the powder of this embodiment is used to form a molded body, the molding may be performed by a known method, for example, at least one method selected from the group consisting of uniaxial pressing, cold isostatic pressing, slip casting, and injection molding. When a molded body is produced using a resin such as a compound, the resulting molded body may be heat-treated to remove the resin, if necessary. Examples of heat-treatment conditions include a temperature of 400°C or higher and lower than 800°C in air.
[0079] The molded body may be calcined as necessary. Calcination may be performed by heat treatment at a temperature lower than the sintering temperature of the powder, for example, in the air at 800° C. or higher and lower than 1200° C. This produces a calcined body.
[0080] Sintering can be performed by a known method, such as one or more selected from the group consisting of pressure sintering, vacuum sintering, and atmospheric sintering. Sintering is preferably atmospheric sintering because it is simple and easy to apply industrially, and atmospheric sintering at 1200°C to 1550°C in air, preferably 1250°C to 1500°C, is more preferable, and atmospheric sintering at 1300°C to 1450°C in air is even more preferable. In addition, it is preferable not to perform sintering other than atmospheric sintering. The sintering time is arbitrary, but can be exemplified as 0.5 hours to 5 hours.
[0081] Next, a method for producing the powder according to this embodiment will be described.
[0082] The powder of this embodiment may be produced by any method as long as it has the above-mentioned characteristics. A preferred method for producing the powder of this embodiment includes a step of heat-treating a composition containing a zirconia sol containing zirconia having an average sol particle size of 150 nm to 400 nm and containing monoclinic zirconia, and a stabilizer source, at 950° C. to 1250° C. to obtain a calcined powder, and a step of pulverizing the calcined powder.
[0083] A calcined powder, which is a precursor of the powder of this embodiment, is obtained by a process in which a composition containing a zirconia sol containing zirconia having an average sol particle size of 150 nm or more and 400 nm or less and containing monoclinic zirconia, and a stabilizer source is heat-treated at 950°C or more and 1250°C or less to form a calcined powder (hereinafter also referred to as a "powder calcination process").
[0084] In the powder calcination process, heat treatment is performed at 950°C to 1250°C, or more preferably 1000°C to 1250°C. Heat treatment at 950°C or higher results in powder that is easily densified by atmospheric sintering. On the other hand, heat treatment at 1250°C or lower results in powder that is easily dispersed by pulverization. The heat treatment time varies depending on the heat treatment temperature, but can be, for example, 30 minutes to 2 hours.
[0085] The heat treatment may be performed in any atmosphere, for example, any atmosphere selected from the group consisting of an oxidizing atmosphere, a reducing atmosphere, an inert atmosphere, and a vacuum atmosphere. An oxidizing atmosphere is preferable, and an air atmosphere is more preferable.
[0086] The zirconia sol has an average sol particle size of 150 nm to 400 nm, preferably 180 nm to 400 nm, more preferably 185 nm to 300 nm. The average sol particle size may be 150 nm to 270 nm, further 150 nm to 200 nm, or 190 nm to 400 nm, further 200 nm to 300 nm.
[0087] The zirconia sol contains zirconia containing monoclinic zirconia, and is preferably a zirconia sol containing zirconia made of crystalline zirconia (hereinafter also referred to as "crystalline zirconia sol"), and is more preferably a zirconia sol containing crystalline zirconia whose main phase is monoclinic zirconia.
[0088] Since the zirconia sol tends to be easily pulverized, the amount of zirconium element calculated by the following formula (hereinafter also referred to as "adsorbed zirconium amount") is preferably from 0 to 1 mass%, more preferably from 0 to 0.5 mass%, and even more preferably from 0 to 0.01 mass%.
[0089] W Zr =(m / m0)×100 In the above formula, W Zr is the amount of adsorbed zirconium (mass%). m is the mass (mg) of the amount of zirconium in the filtrate obtained by ultrafiltration of a slurry in which zirconia sol is dispersed in pure water, using an ultrafiltration membrane with a molecular weight cutoff of 500 to 3 million, converted into zirconia (ZrO2). The amount of zirconium in the filtrate can be measured by ICP analysis. m o m and m are the mass (mg) of the zirconia sol before ultrafiltration after heat treatment at 1000°C for 1 hour in air. o The measurements of can be carried out by preparing the same amount of zirconia sol before ultrafiltration.
[0090] The zirconia sol to be subjected to the powder calcination step may be produced by any method as long as it has the above-mentioned characteristics. Examples of the method for producing the zirconia sol include at least one of a hydrothermal synthesis method and a hydrolysis method. In the hydrothermal synthesis method, a coprecipitate obtained by mixing a zirconium salt with an alkali or the like in the presence of a solvent is heat-treated at 100 to 200°C to obtain a zirconia sol. In the hydrolysis method, a zirconium salt is heated in the presence of a solvent to hydrolyze the zirconium salt, thereby obtaining a zirconia sol. Thus, examples of the zirconia sol include a zirconia sol obtained by a hydrothermal synthesis method or a hydrolysis method, and a zirconia sol obtained by a hydrolysis method is preferably a zirconia sol obtained by a hydrolysis method.
[0091] The precursor used in the method for producing the zirconia sol can be a zirconium salt. The zirconium salt can be one or more selected from the group consisting of zirconium oxychloride, zirconyl nitrate, zirconium chloride, and zirconium sulfate, and is preferably at least one of zirconyl nitrate and zirconium oxychloride, and more preferably zirconium oxychloride.
[0092] Hereinafter, the hydrolysis method will be described as an example of a preferred method for producing the zirconia sol.
[0093] The hydrolysis conditions may be any conditions under which the hydrolysis of the zirconium salt proceeds sufficiently, and examples thereof include boiling and refluxing the aqueous zirconium salt solution for 130 to 200 hours. By carrying out hydrolysis with an anion concentration in the aqueous zirconium salt solution of 0.2 to 0.6 mol / L, or even 0.3 to 0.6 mol / L, the average sol particle size tends to become larger.
[0094] The stabilizer source may be at least one of a stabilizer and a compound that is a precursor thereof, and may be at least one selected from the group consisting of oxides, hydroxides, oxyhydroxides, chlorides, acetates, nitrates, and sulfates that are precursors of stabilizers, and is preferably at least one of chlorides and nitrates. The stabilizer source is preferably at least one of yttria and an yttrium compound that is a precursor thereof. Preferred stabilizer sources (hereinafter, stabilizers that contain yttria, etc., are also referred to as "yttria sources", etc.) include at least one selected from the group consisting of yttrium chloride, yttrium nitrate, and yttrium oxide, and further at least one of yttrium chloride and yttrium oxide. When the stabilizer source is an yttria source, the content of the yttria source in the composition can be, for example, 1.0 mol% or more and 2.5 mol% or less, or even 1.1 mol% or more and 2.0 mol% or less, preferably 1.2 mol% or more and less than 2.0 mol%, and more preferably 1.2 mol% or more and 1.8 mol% or less, as a molar ratio of the yttria source converted into Y2O3 to the sum of the values of zirconium (Zr) and yttrium (Y) in the composition converted into ZrO2 and Y2O3, respectively.
[0095] The composition to be subjected to the powder calcination step may contain the above-mentioned zirconia sol and a stabilizer source, and all or a part of the stabilizer source may be dissolved in the zirconia sol.
[0096] For example, by mixing a zirconium salt and a stabilizer source and hydrolyzing the mixture, or by mixing a zirconium salt, a stabilizer source and an alkali or the like and coprecipitating the mixture, at least a portion of the stabilizer source can be easily dissolved in zirconia.
[0097] The composition to be subjected to the powder calcination step may contain one or more additive component sources selected from the group consisting of an alumina source, a germania source, and a silica source. The additive component source is preferably at least one of an alumina source and a germania source, and is preferably an alumina source.
[0098] The alumina source is at least one of alumina and an aluminum compound that serves as a precursor thereof, and examples thereof include one or more selected from the group consisting of alumina, aluminum hydroxide, aluminum nitrate, and aluminum chloride. Alumina is preferable, and at least one of alumina sol and alumina powder is more preferable.
[0099] The germania source is at least one of germania and a germanium compound which is a precursor thereof, and can be exemplified by one or more selected from the group consisting of germania, germanium hydroxide, and germanium chloride. Germania is preferred, and at least one of germania sol and germania powder is more preferred.
[0100] The silica source is at least one of silica and a silicon compound that serves as a precursor thereof, and examples thereof include one or more types selected from the group consisting of silica and tetraethyl orthosilicate. Silica is preferred, and at least one of silica powder, silica sol, fumed silica, and precipitated silica is more preferred.
[0101] The content of the additive component source is, in terms of the total ratio of the masses of Al, Ge and Si converted into Al2O3, GeO2 and SiO2 to the total masses of Zr, Y, Al, Ge and Si in the composition converted into ZrO2, Y2O3, Al2O3, GeO2 and SiO2, respectively, of 0.05 mass% or more and 30 mass% or less, preferably more than 0.1 mass% and 25 mass% or less, and more preferably 0.2 mass% or more and 20 mass% or less.
[0102] For example, the content of the alumina source can be 0.05% by mass or more and 30% by mass or less, expressed as the ratio of the mass of the alumina source converted into Al2O3 to the total mass of Zr, Y, and Al in the composition converted into ZrO2, Y2O3, and Al2O3, respectively, and is preferably more than 0.1% by mass and 25% by mass or less, and more preferably 0.2% by mass or more and 20% by mass or less.
[0103] The content of the germania source is, as a ratio of the mass of the germania source converted into GeO2 to the total mass of Zr, Y, and Ge in the composition converted into ZrO2, Y2O3, and GeO2, respectively, of 0.05 mass% or more and 30 mass% or less, preferably more than 0.1 mass% and 25 mass% or less, and more preferably 0.2 mass% or more and 20 mass% or less.
[0104] The content of the silica source, expressed as the ratio of the mass of the silica source converted into SiO2 to the total mass of Zr, Y, and Si in the composition converted into ZrO2, Y2O3, and SiO2, respectively, can be 0.05 mass% or more and 30 mass% or less, preferably more than 0.1 mass% and 25 mass% or less, and more preferably 0.2 mass% or more and 20 mass% or less.
[0105] The physical properties of the calcined powder are BET specific surface area of 3m 2 / g or more 15m 2 / g or less, and the monoclinic crystallite size is 20 nm or more and 60 nm or less.
[0106] In the process of pulverizing the calcined powder (hereinafter also referred to as the "pulverization process"), the calcined powder is pulverized. Zirconia with a low stabilizer content is prone to cracking and chipping during sintering. In contrast, by pulverizing the calcined powder in this embodiment, the yield during sintering tends to be high, and the obtained sintered body tends to be less susceptible to hydrothermal degradation.
[0107] In order to obtain a powder of a desired composition, in the pulverization step, instead of the calcined powder, a mixed powder of the calcined powder, the alumina source, and the additive component source may be pulverized. The additive component source may be exemplified by the additive component source described above. When the additive component source is mixed in the pulverization step, the additive component source and the calcined powder may be mixed so that the total of the mass ratio of Al converted to Al2O3, the mass ratio of Ge converted to GeO2, and the mass ratio of Si converted to SiO2 with respect to the total mass of Zr, Y, and one or more selected from the group of Al, Ge, and Si in the mixed powder converted to ZrO2, Y2O3, Al2O3, GeO2, and SiO2 is 0.05 mass% or more and 30 mass% or less, preferably more than 0.1 mass% and 25 mass% or less, more preferably 0.2 mass% or more and 20 mass% or less.
[0108] The pulverization method may be any method, and may be at least one of wet pulverization and dry pulverization, and is preferably wet pulverization. Specific examples of wet pulverization include one or more selected from the group consisting of ball mills, vibration mills, and continuous media stirring mills, and is preferably ball mills. Examples of pulverization conditions using a ball mill include mixing the calcined powder with a solvent to form a slurry in which the mass ratio of the calcined powder to the slurry mass is 30 mass% or more and 60 mass% or less, and pulverizing the slurry for 10 hours or more and 100 hours or less using zirconia balls with a diameter of 1 mm or more and 15 mm or less as a pulverization medium.
[0109] After the wet grinding, the mixture may be dried to obtain a powder by any method. Drying conditions include, for example, in air at 110°C to 130°C.
[0110] In order to improve the handling of the powder, the method for producing the powder of this embodiment may include a step of granulating the powder (hereinafter, also referred to as a "granulation step"). The granulation may be performed by any method, but an example is spray granulation of a slurry in which the powder is mixed with a solvent. The solvent is at least one of water and alcohol, and preferably water. The granulated powder (hereinafter, also referred to as "powder granules") has an average granule diameter of 30 μm or more and 80 μm or less, and further has a bulk density of 1.00 g / cm. 3 More than 1.40g / cm 3 Below that, 1.10g / cm 3 More than 1.30g / cm 3 The following are some of the reasons: EXAMPLES
[0111] The present disclosure will be described below using examples, but the present disclosure is not limited to these examples. (average sol particle size) The average sol particle size of the zirconia sol was measured using a dynamic light scattering particle size distribution analyzer (Device name: UPA-UT151, manufactured by Microtrack Bell Co., Ltd.) As a pretreatment of the sample, the solution containing hydrated zirconia sol was suspended in pure water and dispersed for 3 minutes using an ultrasonic homogenizer. (The monoclinic and tetragonal crystal ratios of the powder, D t and D. m ) An XRD pattern of the powder sample was obtained using a general X-ray diffractometer (product name: Ultima II V, manufactured by Rigaku Corporation). The conditions for the XRD measurement were as follows: Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ=26°~33°
[0112] Using the obtained XRD pattern and the calculation program "PRO-FIT", the monoclinic crystal ratio, tetragonal crystal ratio, and D t and D. m asked for. (BET specific surface area) The BET specific surface area of the powder sample was measured using a general flow-type automatic specific surface area measurement device (device name: FlowSorb III2305, manufactured by Shimadzu Corporation) and nitrogen as the adsorption gas in accordance with the method of JIS R 1626-1996. Prior to the measurement, the powder sample was degassed in air at 250°C for 30 minutes as pretreatment. (Particle size distribution measurement) The volumetric particle size distribution curve of the powder sample was measured using the HRA mode of a Microtrac particle size distribution analyzer (product name: MT3000II, manufactured by Microtrac Bell Co., Ltd.), and the median diameter was measured. Prior to the measurement, the powder sample was suspended in pure water and dispersed for 10 minutes using an ultrasonic homogenizer as a pretreatment. (Molded object density) The mass of the compact sample was measured with a balance, and the volume was measured with a caliper to determine the dimensions. The actual density was calculated from the obtained mass and volume. The theoretical density was calculated from the formulas (5) to (8), and the relative density (%) was calculated from the value of the actual density (ρ) relative to the theoretical density (ρ0), which was used as the compact density.
[0113] (Monoclinic rate and monoclinic intensity ratio of sintered body) The sintered samples were subjected to XRD measurement under the same conditions as those for the powder samples. Using the obtained XRD patterns and the calculation program "PRO-FIT", the monoclinic rate and monoclinic intensity ratio were calculated by formulas (1) and (3), respectively. For the XRD measurement, the sintered samples were used in which the surface was ground using a surface grinder, then automatically polished with waterproof paper (No. 800), then with diamond slurry with an average particle size of 3 μm, and finally with colloidal silica with a particle size of 0.03 μm, in that order, to a mirror finish with a surface roughness (Ra) of ≦0.04 μm. An automatic polishing machine (machine name: MECATECH 334, manufactured by PRESI) was used for the automatic polishing. (Sintered body density) The actual density of the sintered body samples was measured by the Archimedes method. Prior to the measurement, the mass of the dried sintered body was measured, and then the sintered body was placed in water and boiled for 1 hour as pretreatment. The theoretical density was calculated from the formulas (5) to (8), and the relative density (%) was calculated from the value of the actual density (ρ) relative to the theoretical density (ρ0), which was used as the density of the sintered body.
[0114] (Average grain size) The average crystal grain size was determined by the planimetric method using the SEM observation image of the sintered body sample obtained by field emission scanning electron microscope observation. That is, a circle with a known area was drawn on the SEM observation image, and the number of crystal grains within the circle (Nc) and the number of crystal grains on the circumference of the circle (Ni) were counted. The total number of crystal grains (Nc+Ni) was set to 250±50, and the average crystal grain size was calculated using the following formula. Average grain size=(Nc+(1 / 2)×Ni) / (A / M 2 ) In the above formula, Nc is the number of crystal grains within a circle, Ni is the number of crystal grains on the circumference of the circle, A is the area of the circle, and M is the magnification of the scanning electron microscope observation (5000 times). When the number of crystal grains (Nc + Ni) in one SEM observation image was less than 200, (Nc + Ni) was set to 250 ± 50 using multiple SEM observation images. Prior to the measurement, the sintered samples were pretreated by mirror polishing and thermal etching. For mirror polishing, the surface of the sintered samples was ground using a surface grinder, and then polished using diamond abrasives with average grain sizes of 9 μm, 6 μm, and 1 μm in sequence using a mirror polishing machine.
[0115] (Fracture toughness value) The fracture toughness value of the sintered compact samples was measured according to the SEPB method specified in JIS R 1607. Measurements were performed using columnar sintered compact samples with a support distance of 30 mm, width of 4 mm and thickness of 3 mm, and the average value of 10 measurements was taken as the fracture toughness value.
[0116] (Bending strength) The bending strength of the sintered body samples was measured by a three-point bending test in accordance with JIS R 1601. The measurement was performed using a columnar sintered body sample with a support distance of 30 mm, width of 4 mm, and thickness of 3 mm, and the bending strength was calculated by averaging 10 measurements. (Total light transmittance) The total light transmittance was measured using a spectrophotometer (device name: V-650, manufactured by JASCO Corporation) according to a method conforming to JIS K 7361. A disk-shaped sample was used for the measurement. Prior to the measurement, both sides of the sample were polished to a thickness of 1 mm and a surface roughness (Ra) of 0.02 μm or less. Light with wavelengths of 220 to 850 nm was transmitted through the sample and collected with an integrating sphere to measure the transmittance at each wavelength, and the transmittance at a wavelength of 600 nm was taken as the total light transmittance.
[0117] Example 1 An aqueous solution of zirconium oxychloride with a zirconium concentration and a chloride ion concentration of 0.4 mol / L was hydrolyzed. The aqueous solution after hydrolysis was ultrafiltered using an ultrafiltration membrane (molecular weight cutoff: 6000) to obtain a zirconia sol with an average sol particle size of 250 nm. Zr was below the detection limit (0.01% by mass or less).
[0118] Yttrium chloride hexahydrate and an aqueous ammonia solution were added to the ultrafiltered zirconia sol solution so that the yttria content was 1.6 mol %, to obtain a precipitate. The obtained precipitate was washed with pure water and dried in the air, and then calcined in the air at a calcination temperature of 1025°C for 2 hours to obtain a calcined powder. The BET specific surface area of the obtained calcined powder was 12.5 m 2 / g, and the monoclinic crystallite size was 35 nm.
[0119] The calcined powder was mixed with pure water to form a slurry, which was then ball milled using zirconia balls and dried at 120°C in air to obtain a powder of yttria-containing zirconia with an yttria content of 1.6 mol%, which was used as the powder of this example. In this powder, all of the yttria was dissolved in zirconia, and the crystal phases were monoclinic zirconia and tetragonal zirconia. The median diameter was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.33 μm, and the particle size peak ratio was 0.39.
[0120] The powder of this example was molded under a pressure of 70 MPa and subjected to a CIP treatment under a pressure of 196 MPa to produce a compact. The resulting compact was sintered under atmospheric pressure at a sintering temperature of 1300° C. for 2 hours in the air to produce a sintered body.
[0121] Example 2 A powder containing 0.25% by mass of alumina in terms of Al2O3 and the remainder being 1.6 mol% yttria-containing zirconia was obtained in the same manner as in Example 1, except that a mixed powder of the calcined powder and 0.25% by mass of alumina sol in terms of Al2O3 was ball milled. The median diameter of the powder in this example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.32 μm, and the particle size peak ratio was 0.37.
[0122] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1250°C.
[0123] Example 3 A powder containing 0.25% by mass of alumina calculated as Al2O3 and the remainder being 1.6 mol% yttria-containing zirconia was obtained in the same manner as in Example 1, except that the calcination temperature was set to 1130°C and a mixed powder of the calcined powder and 0.25% by mass of alumina sol calculated as Al2O3 was subjected to a ball mill treatment.
[0124] The BET specific surface area of the calcined powder obtained was 6.7m 2 The powder of this example had a median diameter of 0.18 μm, a volumetric particle size distribution curve with peaks at particle sizes of 0.14 μm and 0.36 μm was a bimodal distribution, and the particle size peak ratio was 0.85.
[0125] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used.
[0126] Example 4 A powder containing 0.25 mass% alumina in terms of Al2O3 and the remainder being 2 mol% yttria-containing zirconia was obtained in the same manner as in Example 1, except that yttrium chloride hexahydrate was added to the zirconia sol solution after ultrafiltration so that yttria was 2 mol%, and a mixed powder of the calcined powder and an alumina sol of 0.25 mass% in terms of Al2O3 was ball milled. The median diameter of the powder in this example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.33 μm, and the particle size peak ratio was 0.33.
[0127] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1500°C.
[0128] Example 5 A powder containing 20 mass% alumina in terms of Al2O3, with the remainder being 1.6 mol% yttria-containing zirconia, was obtained in the same manner as in Example 1, except that a mixed powder of the calcined powder and 20 mass% alumina powder calculated as Al2O3 was subjected to ball milling. The median diameter of the powder in this example was 0.15 μm, and the volumetric particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.35 μm, with a particle size peak ratio of 0.41. The crystallite diameter (D t ) was 42 nm.
[0129] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1350°C.
[0130] Example 6 A powder containing 20% by mass of alumina in terms of Al2O3 and the remainder being 1.6 mol% yttria-containing zirconia was obtained in the same manner as in Example 1, except that the calcination temperature was set to 1130°C and a mixed powder of the calcined powder and 20% by mass of alumina powder in terms of Al2O3 was subjected to ball milling. The median diameter of the powder in this example was 0.16 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.35 μm, and the particle size peak ratio was 0.67.
[0131] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1400°C.
[0132] Example 7 A powder containing 5% by mass of alumina in terms of Al2O3 and the remainder being 2 mol% yttria-containing zirconia was obtained in the same manner as in Example 1, except that yttrium chloride hexahydrate was added to the zirconia sol solution after ultrafiltration so that yttria was 2 mol%, and a mixed powder of the calcined powder and 5% by mass of alumina sol in terms of Al2O3 was ball milled. The median diameter of the powder in this example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.35 μm, and the particle size peak ratio was 0.41.
[0133] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1500°C.
[0134] Example 8 A powder containing 0.5% by mass of alumina in terms of Al2O3 and the remainder being 1.6 mol% yttria-containing zirconia was obtained in the same manner as in Example 1, except that a mixed powder of the calcined powder and 0.5% by mass of alumina sol in terms of Al2O3 was ball milled. The median diameter of the powder in this example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.32 μm, and the particle size peak ratio was 0.49.
[0135] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1250°C.
[0136] Example 9 A powder containing 1% by mass of alumina in terms of Al2O3 and the remainder being 1.6 mol% yttria-containing zirconia was obtained in the same manner as in Example 1, except that a mixed powder of the calcined powder and 1% by mass of alumina sol in terms of Al2O3 was ball milled. The median diameter of the powder in this example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.34 μm, and the particle size peak ratio was 0.49.
[0137] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1250°C.
[0138] Example 10 A powder containing 0.25% by mass of germanium oxide in GeO2 equivalent and the remainder being 1.6 mol% yttria-containing zirconia was obtained in the same manner as in Example 1, except that a mixed powder of the calcined powder and 0.25% by mass of germanium oxide in GeO2 equivalent was ball milled. The median diameter of the powder in this example was 0.14 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.34 μm, and the particle size peak ratio was 0.37.
[0139] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1250°C.
[0140] Example 11 A powder containing 0.25% by mass of silica in terms of SiO2 and the remainder being 1.6 mol% yttria-containing zirconia was obtained in the same manner as in Example 1, except that a mixed powder of the calcined powder and 0.25% by mass of silica sol in terms of SiO2 was ball milled. The median diameter of the powder in this example was 0.18 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.35 μm, and the particle size peak ratio was 0.89.
[0141] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1350°C.
[0142] Example 12 A powder containing 0.25% by mass of alumina in terms of Al2O3, 0.25% by mass of germanium oxide in terms of GeO2, and the remainder being 1.6 mol% yttria-containing zirconia was obtained in the same manner as in Example 1, except that a mixed powder of the calcined powder, 0.25% by mass of alumina sol in terms of Al2O3, and 0.25% by mass of germanium oxide in terms of GeO2 was ball milled. The median diameter of the powder in this example was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.34 μm, and the particle size peak ratio was 0.37.
[0143] A green body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1200°C.
[0144] Comparative Example 1 An aqueous solution of zirconium oxychloride having a zirconium concentration of 0.37 mol / L and a chloride ion concentration of 0.74 mol / L, respectively, was hydrolyzed. The aqueous solution after hydrolysis was ultrafiltered using an ultrafiltration membrane (molecular weight cutoff: 6000) to obtain a zirconia sol having an average sol particle size of 100 nm. Zr was 9% by mass.
[0145] Yttrium chloride hexahydrate and an aqueous ammonia solution were added to the ultrafiltered zirconia sol solution so that the yttria content was 2 mol %, to obtain a precipitate. The obtained precipitate was washed with pure water, dried in the air, and then calcined in the air at a calcination temperature of 1000°C for 2 hours to obtain a calcined powder.
[0146] The calcined powder was mixed with pure water to form a slurry, which was then ball milled using zirconia balls and dried at 120°C in air to obtain a powder made of yttria-containing zirconia with an yttria content of 2 mol%, which was used as the powder for this comparative example.
[0147] The powder of this comparative example was molded under a pressure of 70 MPa and subjected to a CIP treatment under a pressure of 196 MPa to produce a compact. The resulting compact was sintered under atmospheric pressure at a sintering temperature of 1450° C. for 2 hours in the air to produce a sintered body.
[0148] Comparative Example 2 A powder containing 0.25 mass% alumina in terms of Al2O3 and the remainder being 2 mol% yttria-containing zirconia was obtained in the same manner as in Comparative Example 1, except that a mixed powder of the calcined powder and 0.25 mass% alumina powder calculated as Al2O3 was subjected to ball milling.
[0149] A green body and a sintered body were obtained in the same manner as in Comparative Example 1, except that the powder was used.
[0150] Comparative Example 3 A mixture of the calcined powder and 5% by mass of alumina powder calculated as Al2O3 was subjected to ball milling in the same manner as in Comparative Example 1. The balance was 2 mol % yttria-containing zirconia powder.
[0151] A green body and a sintered body were obtained in the same manner as in Comparative Example 1, except that the powder was used.
[0152] Comparative Example 4 A powder consisting of 0.5 mol % yttria-containing zirconia was obtained in the same manner as in Example 1, except that yttrium chloride hexahydrate and an aqueous ammonia solution were added to the zirconia sol aqueous solution after ultrafiltration so that the yttria content was 0.9 mol % to obtain a precipitate.
[0153] The powder was pressed in a mold at a pressure of 70 MPa and subjected to CIP treatment at a pressure of 196 MPa to produce a compact. The resulting compact was sintered at atmospheric pressure for 2 hours at a sintering temperature of 1300°C in air to produce a sintered body, but the density was low and many cracks were generated, making it impossible to evaluate the properties of the sintered body.
[0154] The evaluation results of the powders of these Examples and Comparative Examples are shown in Table 1, and the evaluation results of the sintered bodies are shown in Table 2.
[0155] [Table 1]
[0156] From the above table, it can be seen that the powders in the examples and comparative examples 1 to 3 have the same stabilizer content (yttria content) and additive content, but the powders in the comparative examples 1 to 3 have the same stabilizer content (yttria content) and additive content. m It can be seen that the ratio of monoclinic crystals is low and the D m It can be seen that is small.
[0157] [Table 2]
[0158] From the above table, it can be seen that the green density is 49% or more, even 50% or more in the Examples, and less than 49% or even less than 48% in the Comparative Examples, and the powder of the Examples has high packing property. On the other hand, the sintered density of the sintered body with a stabilizer content of 1.0 mol% or more is about the same in both the Examples and the Comparative Examples, but the fracture toughness value of the Examples is 6.5 MPa m 0.5 The fracture toughness value of the comparative example was 6 MPa m 0.5 It is found that the powder of this example can be used to obtain a sintered body having high fracture toughness by normal pressure sintering. The sintered body of Comparative Example 1 does not have an XRD peak corresponding to the (111) plane of monoclinic zirconia, so the monoclinic intensity ratio could not be calculated. Furthermore, the sintered body of Comparative Example 4 contains a large amount of defects such as cracks, and the sintered body collapses when processed into a measurement sample such as mirror polishing, so that measurements other than the sintered body density could not be performed.
[0159] The fracture toughness of the sintered bodies of Examples 1 and 5 was measured according to the IF method specified in JIS R1607. The fracture toughness measured by the IF method was 17.9 MPa m 1 / 5 and 11.1 MPa m 1 / 5 Although the degree of increase in fracture toughness measured by the IF method and the SEPB method differed, the fracture toughness measured by the IF method was higher than that measured by the SEPB method in both cases.
[0160] Example 13 A powder was obtained in the same manner as in Example 1. A sintered body was obtained in the same manner as in Example 1, except that the obtained powder was used and the sintering temperature was 1400°C.
[0161] Example 14 A powder was obtained in the same manner as in Example 2. A sintered body was obtained in the same manner as in Example 2, except that the obtained powder was used and the sintering temperature was 1350°C.
[0162] Example 15 A powder was obtained in the same manner as in Example 3. A sintered body was obtained in the same manner as in Example 3, except that the obtained powder was used and the sintering temperature was 1400°C.
[0163] Example 16 A powder was obtained in the same manner as in Example 5. A sintered body was obtained in the same manner as in Example 5, except that the obtained powder was used and the sintering temperature was 1500°C.
[0164] Example 17 A powder was obtained in the same manner as in Example 6. A sintered body was obtained in the same manner as in Example 6, except that the obtained powder was used and the sintering temperature was 1500°C.
[0165] Example 18 A powder was obtained in the same manner as in Example 8. A sintered body was obtained in the same manner as in Example 8, except that the obtained powder was used and the sintering temperature was 1350°C.
[0166] Example 19 A powder was obtained in the same manner as in Example 9. A sintered body was obtained in the same manner as in Example 9, except that the obtained powder was used and the sintering temperature was 1350°C.
[0167] Example 20 A powder was obtained in the same manner as in Example 10. A sintered body was obtained in the same manner as in Example 10, except that the obtained powder was used and the sintering temperature was 1350°C.
[0168] Example 21 A powder was obtained in the same manner as in Example 12. A sintered body was obtained in the same manner as in Example 12, except that the obtained powder was used and the sintering temperature was 1250°C.
[0169] Example 22 A powder was obtained in the same manner as in Example 12. A sintered body was obtained in the same manner as in Example 12, except that the obtained powder was used and the sintering temperature was 1350°C.
[0170] Comparative Example 5 A powder was obtained in the same manner as in Comparative Example 1. A sintered body was obtained in the same manner as in Comparative Example 1, except that the obtained powder was used and the sintering temperature was 1500°C.
[0171] [Table 3]
[0172] The fracture toughness of the sintered body of the example measured by the SEPB method is 7 MPa m 0.5 That was all.
[0173] Measurement example 1 (hydrothermal degradation test) A sintered body was obtained in the same manner as in Example 2, mirror-polished, and then immersed in hot water at 140°C to carry out a hydrothermal degradation test, and the monoclinic crystal ratio of the sintered body surface was determined after 6 and 10 hours of immersion. In addition, as a comparative measurement example, a zirconia sintered body containing 3 mol% yttria was treated and evaluated in the same manner. The results are shown in the table below.
[0174] The sintered body of the comparative measurement example was produced by molding a powder of zirconia containing 3 mol% yttria, obtained in the same manner as in Comparative Example 1, except that yttrium chloride hexahydrate was added to the ultrafiltered zirconia sol aqueous solution so that the yttria content was 3 mol%. The molded body was then subjected to a die press at a pressure of 70 MPa and a CIP treatment at a pressure of 196 MPa, and this was then sintered at normal pressure in air at a sintering temperature of 1500°C for 2 hours. The fracture toughness value of the sintered body of the comparative measurement example was 4.8 MPa m 0.5 It was.
[0175] [Table 4]
[0176] In both the measurement example and the comparative measurement example, the main crystal phase of the sintered body before the hydrothermal degradation test was tetragonal zirconia. The sintered body deteriorates due to the phase transition of tetragonal zirconia to monoclinic zirconia during the hydrothermal degradation test. Compared to the comparative measurement example, the measurement example has a sintered body with a low stabilizer content, but the monoclinic ratio after the hydrothermal degradation test is low, indicating that the sintered body is less susceptible to deterioration. Note that the sintered body of the comparative measurement example before the hydrothermal degradation test had a monoclinic ratio of 0% and a tetragonal ratio of 70%, with the remainder being cubic, so the remaining tetragonal ratio (△T%) was 4%, and it is believed that almost all of the tetragonal zirconia of the sintered body underwent a phase transition to monoclinic zirconia after the 10-hour hydrothermal degradation test. In contrast, the sintered body in the measurement example before the hydrothermal degradation test had a tetragonal crystal ratio of 94% and a monoclinic crystal ratio of 6%, and therefore the remaining tetragonal crystal ratio (△T%) was 85%. Furthermore, it is considered that the sintered body contained a large amount of tetragonal zirconia that did not undergo phase transition even after the 10-hour hydrothermal degradation test.
[0177] Measurement example 2 (residual tetragonal crystal ratio) The sintered bodies of Examples 1 and 13 and Comparative Examples 1 and 5 were mirror-polished, and then immersed in hot water at 140° C. for 6 hours to determine the residual tetragonal crystal ratio. The results are shown in the table below.
[0178] [Table 5]
[0179] The residual tetragonal crystal ratio of the sintered bodies of the examples was 65% or more, and it is clear that transformation from tetragonal zirconia to monoclinic zirconia was less likely to occur than in the comparative examples in which the stabilizer content was higher.
[0180] Measurement example 3 (residual tetragonal crystal ratio) The sintered bodies of Examples 2 to 4, 14 and 15 and Comparative Example 2 were mirror-polished and then immersed in hot water at 140° C. for 6 hours to determine the residual tetragonal crystal ratio. The results are shown in the table below.
[0181] [Table 6]
[0182] The residual tetragonal rate of the sintered bodies of the examples is 65% or more, and it is found that the transformation from tetragonal zirconia to monoclinic zirconia is less likely to occur compared to the comparative examples. Furthermore, it is found that the residual tetragonal rate of the sintered bodies of the examples is high, even though the stabilizer content is the same as that of the comparative example 2 and the sintering temperature is high.
[0183] Measurement example 4 (residual tetragonal crystal ratio) The sintered bodies of Examples 5 to 12, 16 to 22 and Comparative Example 3 were mirror-polished and then immersed in hot water at 140° C. for 6 hours to determine the residual tetragonal crystal ratio. The results are shown in the table below.
[0184] [Table 7]
[0185] The residual tetragonal ratio of the sintered body of the embodiment is 70% or more, and it is found that the transformation from tetragonal zirconia to monoclinic zirconia is less likely to occur compared to the comparative example. In addition, the sintered body of the embodiment 22 is a sintered body containing a total of 0.5 mass% of alumina and germania as added components. It is found that the sintered body of the embodiment 22 shows a residual tetragonal ratio even though it was obtained by sintering at a higher temperature compared to the sintered body of the embodiment 6 containing 20 mass% alumina.
[0186] Furthermore, from Examples 1, 3 and 6 (and Examples 5, 18 and 19) in which the sintering temperature and stabilizer content were the same, there was a tendency that the residual tetragonal crystal ratio increased as the content of the added component (alumina) increased.
[0187] Measurement example 5 (total light transmittance) The total light transmittance was measured using the sintered bodies of Examples 2, 8, 9 and 14, and Comparative Example 2. The results are shown in the table below.
[0188] [Table 8]
[0189] Although the sintered bodies of the Examples all had an additive component content of 0.2 mass% or more, the total light transmittance was 25% or more and 40% or less. Moreover, in Examples 2 and 14, the total light transmittance increased with increasing sintering temperature. In contrast, the sintered body of Comparative Example 2 had a total light transmittance of less than 20% despite the higher sintering temperature.
[0190] Furthermore, the sintered body of Example 2 was processed to a thickness of 0.2 mm, and the total light transmittance was measured in the same manner. As a result, the total light transmittance at a thickness of 0.2 mm was 46%. When an attempt was made to process the sintered body of Comparative Example 2 in the same manner, the sintered body broke during processing, and it was not possible to obtain a measurement sample with a thickness of 0.2 mm or less.
[0191] Measurement example 6 (linear transmittance) The sintered bodies of the examples were each processed to a thickness of 0.09 mm. All of them could be processed to a measurement specimen having a thickness of 0.09 mm without cracks. The sintered bodies of the comparative examples could not be processed to a thickness of 0.2 mm because defects such as cracks and breaks occurred during processing.
[0192] The linear transmittance of the sintered body having a sample thickness of 0.09 mm was measured. The linear transmittance values of the main examples are shown in the table below.
[0193] [Table 9]
[0194] It can be seen from Examples 2, 3 and 14 that the linear transmittance decreases with increasing sintering temperature. It can also be seen that the sintered body of Example 1, which does not contain alumina, has a high linear transmittance, and the sintered body of Example 8 has a low linear transmittance, compared to Example 3. Furthermore, a comparison of Examples 11, 14, 20 and 21 shows that the linear transmittance differs depending on the type of additive.
[0195] Measurement example 7 (compound evaluation) Compounds were prepared using the powders of Examples 2 and 3, respectively. That is, the powders were dried at 150°C for at least 1 hour, and then the powders and acrylic resin were added to a kneader (apparatus name: Lab Kneader Mill TDR-3, manufactured by Toshin Co., Ltd.) so that the mass of the powder relative to the mass of the obtained compound was 85 mass%, and the compounds were obtained by kneading at 160°C. The kneadability of the compounds was evaluated by measuring the torque (N·m) applied to the kneader 15 minutes after the start of kneading. The smaller the torque value, the easier the compound was to knead, i.e., the better the kneadability.
[0196] The fluidity was evaluated by measuring the flow rate of the compound sample using a flow tester. A general flow tester (device name: Flow Tester CFT500D, manufactured by Shimadzu Corporation) was used for the measurement, and the compound was filled into a syringe. A load was applied to the compound under the following conditions, and the volume velocity (cm 3 The flowability was confirmed by measuring the volume velocity (V / s). The measurement conditions are as follows. The higher the volume velocity, the easier the compound flows in a molten state, i.e., the better the flowability of the compound.
[0197] Syringe area: 1cm 2 Die hole diameter: 1mm Die length: 2mm Load capacity: 50kg Measurement temperature: 160℃ Compound density: 3.0g / cm 3 In addition, as a comparative measurement example, the BET specific surface area is 15.0 m 2 A zirconia powder containing 3 mol% yttria, with a molecular weight of 1.01 g / g and an average particle size (median size) of 1.1 μm, was similarly evaluated. The evaluation results of the compound are shown in the table below. The powder of the comparative measurement example had poor kneadability and could not be kneaded at 160°C. Therefore, the kneadability of the comparative measurement example in the table below shows the value when kneaded at 170°C.
[0198] [Table 10]
[0199] Compared to the powder of the Comparative Example, the powder of Example 3, which has a low BET specific surface area, was excellent in both kneadability and fluidity, and the fluidity was particularly high. Furthermore, although the powders of Example 2 and Comparative Example had similar BET specific surface areas, the powder of Example 2 had extremely high fluidity compared to the powder of the Comparative Example. From these results, it can be seen that the powders of the Examples also have excellent effects as compositions (compounds) consisting of powder and resin.
Claims
1. A zirconia powder comprising a stabilizer, the content of the stabilizer being 1.0 mol % or more and 2.5 mol % or less, the powder containing zirconia having a monoclinic crystal ratio of more than 70%, the crystallite diameter of the monoclinic zirconia being more than 23 nm and 80 nm or less, and the crystal phase of the zirconia containing monoclinic zirconia and tetragonal zirconia.
2. 2. The zirconia powder according to claim 1, wherein the stabilizer is at least one selected from the group consisting of yttria, calcia, magnesia and ceria.
3. The zirconia powder according to claim 1 or 2, wherein the content of the stabilizer is 1.6 mol % or more and 2.0 mol % or less.
4. 4. The zirconia powder according to claim 1, further comprising one or more additive components selected from the group consisting of alumina, germania and silica.
5. The zirconia powder according to claim 4, wherein the content of the additive component is 0.1% by mass or more and 30% by mass or less.
6. BET specific surface area is 6m 2 / g or more 20m 2 The zirconia powder according to any one of claims 1 to 5, wherein the zirconia powder has a molecular weight of less than 1 / g.
7. The zirconia powder according to any one of claims 1 to 6, having a median diameter of 0.05 µm or more and 0.3 µm or less.
8. 8. The zirconia powder according to claim 1, wherein the volume particle size distribution curve is a multimodal distribution.
9. 9. The zirconia powder according to claim 1, which is uniaxially pressed at a pressure of 70±5 MPa and then cold isostatically pressed at a pressure of 196±5 MPa to form a green body, the green body having a relative density of 49% or more and 56% or less.
10. A composition comprising the zirconia powder according to any one of claims 1 to 9 and a resin.
11. A precursor of a calcined body comprising the zirconia powder according to any one of claims 1 to 9.
12. A precursor of a sintered body comprising the zirconia powder according to any one of claims 1 to 9.
13. 10. The method for producing a zirconia powder according to claim 1 , comprising: a step of heat-treating a composition containing a zirconia sol containing zirconia having an average sol particle size of 150 nm or more and 400 nm or less, containing monoclinic zirconia, and a stabilizer source, at 950° C. or more and 1250° C. or less to obtain a calcined powder; and a step of pulverizing the calcined powder.
14. A method for producing a sintered body using the zirconia powder according to any one of claims 1 to 9.
Citation Information
Patent Citations
Zirconia powder for thermal spraying
JP1993339698A
Zirconia sintered product and its production and its use
JP1999240757A
Highly durable sintered zirconia and crusher / disperser member using the same
JP2003128461A
Zirconia powder and sintered compact thereof
JP2003192452A
Zirconia powder
JP2004182554A
Cited By
Sintered body, powder, and method for producing the same
JP2024138111A